Extracellular or intracellular application of argiotoxin-636 has inhibitory actions on membrane excitability and voltage-activated currents in cultured rat sensory neurones - Scott, Roderick H.; M. Thatcher, Nicola; Ayar, Ahmet; Mitchell, Simon J.; Pollock, Jamie; T. Gibson, Michael; Blagbrough, Ian S. (My University, 1998)
The whole cell variant of the patch clamp technique was used to investigate the actions of the polyamine amide spider toxin, argiotoxin-636, on the excitability of cultured dorsal root ganglion neurones. Synthesized argiotoxin-636 (0.1-100 ?M) reduced neuronal excitability when applied to the extracellular environment by low pressure ejection or to the intracellular environment via the patch pipette solution. The toxin prolonged the duration of evoked action potentials and reduced the peak amplitude of action potentials. Intracellular and extracellular application of argiotoxin-636 also decreased the number of action potentials evoked in response to 800-ms depolarizing current commands. This action of the toxin was mimicked by 100 ?M tetraethylammonium. Extracellular application of argiotoxin-636 inhibited voltage-activated K+ currents in a dose-dependent manner over the complete voltage range. This inhibition occurred without any significant changes in the voltage dependence of activation or inactivation. Intracellular application of argiotoxin-636, during 5-10 min of whole cell recording, also inhibited voltage-activated K+ currents without changing the voltage dependence of activation or steady-state inactivation. Extracellular or intracellular spermidine (250 ?M) reversibly attenuated the inhibitory actions of extracellular argiotoxin-636. Argiotoxin-636 also inhibited voltage-activated Na+ currents; this effect was dependent on repeated activation of the currents and the period during which the neurones were in culture. We conclude that application of argiotoxin-636 to either the extracellular or intracellular environment reduced excitability of cultured sensory neurones from neonatal rats and that this involved inhibition of both voltage-activated K+ and Na+ currents. The data suggest that the toxin was more effective at attenuating action potentials when neurones were repeatedly excited, and that access to inhibitory sites of action on the voltage-activated ion channels can be achieved from the inside of the neurone. Copyright (C) 1998 Elsevier Science Ltd.
Keywords: Argiotoxin-636; Dorsal root ganglion; Polyamine; Spermidine; Spider toxin; Voltage-activated potassium currents